2019
DOI: 10.1177/0011128719850502
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Chinese Police Officer Decision-Making in Cases of Domestic Violence

Abstract: The purpose of the current study is to uncover whether extralegal factors play a significant role in Chinese police officers’ decision-making in response to a hypothetical incident of domestic violence (DV). Data were collected from a sample of Chinese police officers located in southwestern China. Ordinary least squares (OLS) regression analyses were conducted to examine the relationship between the attitudes and beliefs of police officers and their decision-making in DV (i.e., recommend putting suspect into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…These findings showing restraint and hesitancy of police officers when getting involved in domestic disputes were also reported in a study by Qu et al 13 where Chinese police officers did not give importance or priority to dispensing resources to deal with this issue and would rather have the issue solved by mediation. Similar findings are reported by Wang et al 14 in China where police are more content with giving oral or written warnings to perpetrators instead of adopting a heavier handed approach. However two separate studies attributed this attitude with the country's overall method to resolving domestic violence by using local committees, informal meetings and court systems to mediate and resolve disputes.…”
Section: Resultssupporting
confidence: 87%
“…These findings showing restraint and hesitancy of police officers when getting involved in domestic disputes were also reported in a study by Qu et al 13 where Chinese police officers did not give importance or priority to dispensing resources to deal with this issue and would rather have the issue solved by mediation. Similar findings are reported by Wang et al 14 in China where police are more content with giving oral or written warnings to perpetrators instead of adopting a heavier handed approach. However two separate studies attributed this attitude with the country's overall method to resolving domestic violence by using local committees, informal meetings and court systems to mediate and resolve disputes.…”
Section: Resultssupporting
confidence: 87%
“…Police officers tend to make peace and find an acceptable solution to please both parties instead of an arrest. Consequently, the handling of domestic dispute and violence is not as formal as that reported in the United States (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The negative association between dealing with DV incidents and the perception of police work can be the result of how DV incidents are handled in the Chinese culture. There has been a long tradition in China that domestic dispute or violence should be handled informally because it is an "internal" issue (Wang et al, 2019). Police officers tend to make peace and find an acceptable solution to please both parties instead of an arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with research on American police officers (Saunders & Size, 1986), Tang (2003) reported that liberal attitudes toward women's role in society among Chinese police officers were associated with greater responsibility attributed to the abuser and less responsibility attributed to the victim. Wang et al (2019) reported that extralegal factors influence decision-making in a hypothetical DV case among Chinese police officers. More specifically, Chinese officers who held more traditional views of women in Chinese society were more likely to recommend putting the victim into custody and less likely to recommend mediation, which is the typical response to DV in China (He & Hang Ng, 2013;Jiao, 2001).…”
Section: Police Officers' Attitudes Toward DVmentioning
confidence: 99%